Association Rule Mining - Saxena, Priyank; Jain, Rachna (International Journal of Computer Sciences and Engineering, 2014)
Today, Association Rules are considered to be one of the more studied fields under Data Mining. It recently has come under a lot of notice by the data base warehouses. Its main use is to extract interesting associations, co-relations and frequent patterns among the groups of items recorded of the transactional databases or some different form of data storages. In this paper, a categorization and comparison of the different association rule algorithms that are present today is provided.